THE IMPACT OF UZBEKISTAN'S FOREIGN DEBT ON THE GROSS DOMESTIC PRODUCT - Nishonkulov Shohruhxon; Gafurov Khurshid (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This paper examines the impact of Uzbekistan's foreign debt on its Gross Domestic Product (GDP). The country's debt dynamics, economic indicators, and policy responses are analyzed to understand the debt's implications on Uzbekistan's economy. Uzbekistan's external debt has increased significantly over the last decade, and the debt-toGDP ratio has risen, indicating a growing debt burden. The government has implemented policy responses to manage the debt burden, including economic reforms and debt management practices. While foreign borrowing has enabled the government to finance infrastructure projects, it has also increased the debt service obligations, reducing the government's ability to invest in social sectors. The paper concludes that it is essential for the government to continue implementing sound economic policies to ensure debt sustainability and promote long-term economic growth.